Efficacy of laparoscopic-guided transversus abdominis plane block for patients undergoing robotic-assisted gynaecologic surgery: A randomised control trial - Anupama Rajanbabu (Indian Journal of Anaesthesia, 2019)
Background and Aims: Transverse abdominis plane (TAP) block has been used regularly as part of multimodal analgesia for caesarean sections and other lower abdominal surgeries. Adequate postoperative analgesia provided with regional blocks allows faster postoperative recovery and better patient satisfaction. In our study, we are comparing the analgesic efficacy of laparoscopic-guided TAP block with port infiltration using a local anaesthetic in patients undergoing gynaecologic robotic surgeries. Methods: After obtaining approval from the hospital ethics committee, Central Trial Registry of India (CTRI) clearance and written informed consent from patients, this prospective double-blinded randomised control trial was conducted on patients undergoing robotic-assisted gynaecologic surgery under general anaesthesia. Group B patients received bilateral TAP block under direct laparoscopic vision with 15 ml of 0.1% ropivacaine on each side and Group C patients received routine port site infiltration with 30 ml of 0.1% ropivacaine. Postoperative pain score was measured till 24 hours, need for rescue analgesics, complications associated were noted. Independent two sample 't' test, Mann Whitney u test, Chi-square and Fisher's exact test were used for statistical analysis. Results: Pain score was significantly lower in Group B patients up to 24h (P < 0.001). The use of rescue analgesic was also significantly less in group B compared to Group C (P < 0.001). No adverse events were noted in both groups. Conclusion: Laparoscopic-guided TAP block is effective and superior to port site infiltration in providing postoperative analgesia in patients undergoing robotic-assisted gynaecologic surgery.